2020
DOI: 10.1002/cpe.5771
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation analysis of public opinion polarization in a dynamic network environment

Abstract: Summary At present, there are many group incidents on the Internet, which has caused a high level of public opinion. Hot issues on the Internet can often trigger intense discussions among netizens and finally evolve toward bipolarization or multipolarization. This article focuses on the phenomenon of public opinion polarization under the dynamic network. First, the single‐dimensional evaluation system for the JA model was expanded to multidimensional and analyzes the main factors that cause the polarization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Starting from the internal factors of the evolution of public opinion, based on the strength of the relationship between Internet users and the dynamic connection mechanism of network nodes, Yuan et al (2020) found that the strength and change of the relationship between Internet users will affect the interaction of opinions, and then affect the degree and speed of group polarization. Combining factors such as personal expression intention and personal expression ability, Fu et al (2020) discussed the formation and evolution process of online public opinion, and constructed an evolution model of online public opinion taking into account personal emotion.…”
Section: Research On Evolution Stages Of Public Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the internal factors of the evolution of public opinion, based on the strength of the relationship between Internet users and the dynamic connection mechanism of network nodes, Yuan et al (2020) found that the strength and change of the relationship between Internet users will affect the interaction of opinions, and then affect the degree and speed of group polarization. Combining factors such as personal expression intention and personal expression ability, Fu et al (2020) discussed the formation and evolution process of online public opinion, and constructed an evolution model of online public opinion taking into account personal emotion.…”
Section: Research On Evolution Stages Of Public Opinionmentioning
confidence: 99%
“…Starting from the internal factors of the evolution of public opinion , based on the strength of the relationship between Internet users and the dynamic connection mechanism of network nodes, Yuan et al . (2020) found that the strength and change of the relationship between Internet users will affect the interaction of opinions, and then affect the degree and speed of group polarization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on this, Yuan et al. incorporated the relationship strength and its dynamic changes between individuals into the JA model, [ 27 ] studying the polarization process of multi‐dimensional opinions under complex networks. Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the model did not consider the dynamic changes in network structure. Based on this, Yuan et al incorporated the relationship strength and its dynamic changes between individuals into the JA model, [27] studying the polarization process of multi-dimensional opinions under complex networks. Chen et al established a public opinion polarization model considering individual heterogeneity and dynamic integration based on the JA model, [28] investigating the impact of initial cognitive heterogeneity, individual conformity heterogeneity, and the dynamic integration of individual opinions and mainstream social opinions on the speed and outcome of public opinion polarization.…”
Section: Introductionmentioning
confidence: 99%